2019
DOI: 10.48550/arxiv.1908.07974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deterministic Epidemic Models For Ebola Infection With Time-dependent Controls

Abstract: In this paper, we have studied epidemiological models for Ebola infection using nonlinear ordinary differential equations and optimal control theory. We considered optimal control analysis of SIR and SEIR models for the deadly Ebola infection using vaccination, treatment and educational campaign as time-dependent controls functions. We have applied indirect methods to study existing deterministic optimal control epidemic models for Ebola virus disease. These methods in optimal control are based on Hamiltonian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this section, we present the numerical solutions for our optimality problem using the fourth-order runge-kutta forward-backward sweep method. This numerical scheme is very efficient and has been widely used by several authors in simulating their optimal control problems [1,8,[15][16][17]. The details of this scheme can be found in the monograph [10].…”
Section: Numerical Results Of the Optimal Control Model And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present the numerical solutions for our optimality problem using the fourth-order runge-kutta forward-backward sweep method. This numerical scheme is very efficient and has been widely used by several authors in simulating their optimal control problems [1,8,[15][16][17]. The details of this scheme can be found in the monograph [10].…”
Section: Numerical Results Of the Optimal Control Model And Discussionmentioning
confidence: 99%
“…A detailed comprehensive literature of optimal control models in epidemiological modeling and numerical approximation techniques can be found in [10,24]. Several works in literature reveals that epidemic models that are constructed with optimal control problems are appropriate and very useful for suggesting control strategies to curb disease spread, see, e.g., [1,13,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They developed a fourth-order Runge-Kutta method and a nonstandard finite difference scheme for the proposed model and demonstrated that the RK-4 method failed at certain step sizes, while the NSFD scheme conserved all the dynamical properties of the model at large step sizes. Okyere et al examined the optimal control analysis of epidemiological models such as SIR and SEIR using vaccination, treatment, and educational campaigns as time-dependent control functions [29]. They used the forward-backward sweep method with the RK-4 method to explain the optimal system for different control strategies.…”
Section: Introductionmentioning
confidence: 99%